Iraq's Position Towards the 1968 Lebanese Parliamentary ‎Elections - Elham Hatem Turki; Fahmi Ahmed Farhan (مجلة جامعة الأنبار للعلوم الإنسانية)
Aims: This research aims to study the Lebanese parliamentary elections of ‎‎1968 as a prominent political turning point in Lebanon's modern history, and ‎the accompanying internal conflicts and blocs that had a direct impact on ‎Lebanese political life. The research also focuses on analyzing Iraq's official ‎and unofficial stance on these elections, in light of the regional and ‎international political interactions that the region was witnessing at the time. ‎Methodology: The historical-analytical approach was adopted in addressing ‎the subject of the study, through a review of official documents, sources, and ‎statements issued by Iraqi authorities, in addition to what was reported in the ‎Iraqi and Lebanese press during that period. Political data related to the course ‎of the electoral process and the conflict between the various Lebanese forces ‎were also analyzed. Results: The research demonstrated that the Lebanese ‎elections of 1968 were not merely an internal event, but rather reflected a ‎broader political struggle between two main movements: one inclined to ‎maintain the situation as it is, led by Camille Chamoun and Pierre Gemayel, ‎and the other calling for reform and change, led by Kamal Jumblatt and Sabri ‎Hamadeh. Iraq showed clear interest in these elections due to the potential ‎impact of their outcomes on the regional balance of power. The elections ‎reflected in official, diplomatic, and media coverage. Conclusions: The study ‎concluded that Iraq's position on the 1968 Lebanese parliamentary elections ‎stemmed from its vision of its regional role and its support for nationalist and ‎reformist forces in Lebanon. The elections also revealed the fragility of ‎Lebanese political balances amid sectarian divisions and external tensions, ‎making them a pivotal moment in Lebanon's modern political history.‎